2021
DOI: 10.3390/polym13081283
|View full text |Cite
|
Sign up to set email alerts
|

Dual Plasticizer/Thermal Stabilizer Effect of Epoxidized Chia Seed Oil (Salvia hispanica L.) to Improve Ductility and Thermal Properties of Poly(Lactic Acid)

Abstract: The use of a new bio-based plasticizer derived from epoxidized chia seed oil (ECO) was applied in a poly(lactic acid) (PLA) matrix. ECO was used due to its high epoxy content (6.7%), which led to an improved chemical interaction with PLA. Melt extrusion was used to plasticize PLA with different ECO content in the 0–10 wt.% range. Mechanical, morphological, and thermal characterization was carried out to evaluate the effect of ECO percentage. Besides, disintegration and migration tests were studied to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 60 publications
4
16
0
Order By: Relevance
“…Both plasticizers, MBNO and MHO, decrease the T g and T cc of PLA, which is indicative of an increase in the mobility of the polymer chains at lower temperatures, evidencing the plasticizing effect of both maleinized oils [ 45 ]. The same evolution was reported by Dominguez-Candela et al [ 46 ], who employed epoxidized chia oil (ECO) in PLA. On the other hand, no significant variations were observed in T m , showing that after the addition of the plasticizers, the T m remained at values around 150–153 °C for all the samples.…”
Section: Resultssupporting
confidence: 70%
“…Both plasticizers, MBNO and MHO, decrease the T g and T cc of PLA, which is indicative of an increase in the mobility of the polymer chains at lower temperatures, evidencing the plasticizing effect of both maleinized oils [ 45 ]. The same evolution was reported by Dominguez-Candela et al [ 46 ], who employed epoxidized chia oil (ECO) in PLA. On the other hand, no significant variations were observed in T m , showing that after the addition of the plasticizers, the T m remained at values around 150–153 °C for all the samples.…”
Section: Resultssupporting
confidence: 70%
“…Dominguez-Candela and co-authors [ 70 ] have reported a new biobased PLA plasticizer derived from Epoxidized Chia Seed Oil (ECO). PLA with various contents of ECO (0–10 wt.%) was prepared using melt extrusion.…”
Section: Pla’s Modificationsmentioning
confidence: 99%
“…However, the degree of disintegration was delayed by only 14 days. In another work, Dominguez-Candela et al [54] reported an increase of more than 53% in PLA crystallinity when introducing an organic bio plasticizer, but, a disintegration of more than 90%, which is considered by the UNE 20,200 standard as a biodegradable material, was obtained only 3 days later. Therefore, in view of the previous results, and given that in the present study, there is only a 10.6% increase in crystallinity concerning neat PLA, it can be affirmed that a subsequent disintegration process would be practically unaffected, considering the PLA modified by REX as totally biodegradable.…”
Section: Characterization Of the Functionalized Polymersmentioning
confidence: 97%
“…M specifically, PLA samples modified with low alkoxysilane concentrations, O-PLA-A a P-PLA-A, displayed similar thermal stability to neat PLA, breaking down at temperatu around 364-362 °C, whereas higher organosilane contents showed slightly lower deco position temperatures (356-358 °C). As evidenced by 1H-NMR and SEC analyses, th small changes may be associated with ester-alkoxysilane exchange reactions, which curs at high temperature, causing chain scissions via C-H hydrogen transfer reactio [36,[54][55][56][57]. Consequently, lower molar weights and, therefore, lower thermal stabilit were obtained compared to neat PLA.…”
Section: Characterization Of the Functionalized Polymersmentioning
confidence: 99%